Biotechnologically Produced Lavandula angustifolia Mill. Extract Rich in Rosmarinic Acid Resolves Psoriasis-Related Inflammation Through Janus Kinase/Signal Transducer and Activator of Transcription Signaling - Koycheva, Ivanka K.; Vasileva, Liliya V.; Amirova, Kristiana M.; Marchev, Andrey S.; Balcheva-Sivenova, Zhivka P.; Georgiev, Milen I. (Frontiers in Pharmacology, 2021)
Psoriasis is a common skin pathology, characterized by dysregulation of epidermal keratinocyte function attended by persistent inflammation, suggesting that molecules with anti-inflammatory potential may be effective for its management. Rosmarinic acid (RA) is a natural bioactive molecule known to have an anti-inflammatory potential. Here we examined the effect of biotechnologically-produced cell suspension extract of Lavandula angustifolia Mill. (LV) high in RA content as treatment for psoriasis-associated inflammation in human keratinocytes. Regulatory genes from the nuclear factor kappa B (NF-κB) and Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathways were upregulated upon stimulation with a combination of interferon gamma (IFN-γ), interleukin (IL)-17A and IL-22. We also observed that both LV extract and RA could inhibit JAK2, leading to reduced STAT1 phosphorylation. Further, we demonstrated that LV extract inhibited phosphoinositide 3-kinases (PI3K) and protein kinase B (AKT), which could be implicated in reduced hyperproliferation in keratinocytes. Collectively, these findings indicate that the biotechnologically-produced LV extract resolved psoriasis-like inflammation in human keratinocytes by interfering the JAK2/STAT1 signaling pathway and its effectiveness is due to its high content of RA (10%). Hence, both LV extract and pure RA possess the potential to be incorporated in formulations for topical application as therapeutic approach against psoriasis.